2009
DOI: 10.1111/j.1601-0825.2008.01511.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation of bone turnover markers to periodontal disease and jaw bone morphology in elderly Japanese subjects

Abstract: In conclusion, this study suggests that there is a significant relation of bone turnover markers to periodontal disease and jaw bone morphology in elderly Japanese subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 38 publications
(42 reference statements)
2
24
1
1
Order By: Relevance
“…In a cross-sectional study of 148 elderly Japanese, Yoshihara et al showed that serum OC level was negatively associated with the percentage of sites with CAL loss of 6 mm or more, suggesting that serum OC may be a useful systemic biomarker for diagnosis of periodontal disease in this population [47]. Ozcaka et al however, failed to find significant association between OC and periodontal status in a Turkish population [36].…”
Section: Biomarkers For Diagnosis Of Diseased Individuals Diagnosis-bmentioning
confidence: 99%
“…In a cross-sectional study of 148 elderly Japanese, Yoshihara et al showed that serum OC level was negatively associated with the percentage of sites with CAL loss of 6 mm or more, suggesting that serum OC may be a useful systemic biomarker for diagnosis of periodontal disease in this population [47]. Ozcaka et al however, failed to find significant association between OC and periodontal status in a Turkish population [36].…”
Section: Biomarkers For Diagnosis Of Diseased Individuals Diagnosis-bmentioning
confidence: 99%
“…Differences in the distribution of bone turnover markers according to the percentage of sites with 6+ mm CAL per person are shown in Table 1. S-OC was significantly lower in the third tertile than in the first and second tertiles after adjusting for smoking habit (males: p = 0.007, females: p = 0.042, ANCOVA) (Yoshihara et al, 2009). …”
Section: Bone Metabolism and Periodontal Diseasementioning
confidence: 99%
“…Bone formation and resorption are coupled events that are necessary to maintain the bone homeostasis. Changes in circulating levels of bone turnover markers have been reported in regards with periodontitis patients [2,3].…”
Section: Introductionmentioning
confidence: 99%